Effect of nintedanib on non‐small cell lung cancer in a patient with idiopathic pulmonary fibrosis: A case report and literature review. Issue 6 (14th April 2020) - Shiratori, Toshihiro; Tanaka, Hisashi; Tabe, Chiori; Tsuchiya, Junichiro; Ishioka, Yoshiko; Itoga, Masamichi; Taima, Kageaki; Takanashi, Shingo; Tasaka, Sadatomo
Abstract : Nintedanib has been approved for the treatment of idiopathic pulmonary fibrosis (IPF). In addition, in EU countries, nintedanib plus docetaxel is used for patients with advanced non‐small cell lung cancer (NSCLC) after first‐line chemotherapy. Here, we report a case of advanced NSCLC in a patient with IPF successfully treated with nintedanib monotherapy. A 69‐year‐old man was diagnosed with NSCLC complicated by IPF. After three lines of chemotherapy, he still had progressive disease. Because his IPF had also progressed, requiring supplemental oxygen, we decided to start best supportive care and introduced nintedanib to treat his IPF. One month later, we observed a partial remission of the primary tumor and pleural disseminations without severe adverse events. Nintedanib monotherapy might therefore be an effective therapeutic choice for NSCLC in patients with IPF who are unable to tolerate cytotoxic chemotherapy. Key points: Efficacy of nintedanib administered in a NSCLC patient with IPF. Nintedanib monotherapy might be a therapeutic option for NSCLC patients with IPF who are unable to tolerate chemotherapy.